Linezolid Intoxication with Extreme Lactate Blood Levels Successfully Treated with Dialytic Treatment in ICU: A Case Report - Schiavoni, Lorenzo; Mattei, Alessia; Pascarella, Giuseppe; Strumia, Alessandro; Nenna, Antonio; Chello, Massimo; Agrò, Felice E. (Recent Advances in Inflammation & Allergy Drug Discovery, 2022)
Introduction: Lactic acidosis is a rare but life-threatening complication associated with prolonged linezolid therapy. No specific treatment is suggested, except for antibiotic therapy interruption. Case Report: A 70-years-old woman faced severe linezolid intoxication after antibiotics therapy initiation for infection of a surgical sternal wound. The patient suffered from a severe increment of blood lactate and thrombocytopenia. She was admitted to ICU twice, and due to dialytic treatment, linezolid and lactate serum levels came back to normality. Conclusion: More studies should be conducted to evaluate the human tissue storage sites of linezolid and the influence of various factors on its clearance and plasma concentrations in critically ill patients.
Keywords: lactate